Epidemiological distribution and genotype characterization of hepatitis C virus and HIV co‐infection in Wuhan, China, where the prevalence of HIV is low. Issue 10 (19th July 2013) - Zhao, Rong; Peng, Jinsong; Tang, Li; Huang, Hanju; Liu, Manqing; Kong, Wenhua; Pang, Beibei
Abstract Little is known about the epidemiological characteristics of HIV/hepatitis C virus (HCV) co‐infection in cities in China with low HIV prevalence. This study evaluated the level of exposure to different risk factors associated with HCV transmission and characterized the distribution of HCV genotypes in 356 HIV‐1‐positive patients in Wuhan, central China. HIV transmission routes were distributed as follows: heterosexual contact, male‐to‐male sexual contact, intravenous drug use, blood transfusion, and unknown route. HCV antibodies were detected by a third‐generation enzyme‐linked immunosorbent assay. HCV‐positive plasmas were subjected to RNA extraction, RT‐PCR amplification, and sequencing. Phylogenetic analysis characterized HCV subtypes and the evolutionary origin of circulating HCV strains. Ninety‐two of 356 (25.8%) patients infected with HIV were anti‐HCV‐positive. Among co‐infected patients, the predominant risk for HCV transmission was intravenous drug use (87.3%). Six HCV subtypes (1a, 1b, 2a, 3a, 3b, and 6a) were detected. HCV genotype 6a was most prevalent, occurring in 39.3% of all patients, followed by genotypes 1b (24.7%), 3b (18.0%), and 3a (9.8%). The least frequent genotypes were 1a (4.9%) and 2a (3.3%). Intravenous drug use was strongly associated with genotype 6a, and infection by blood or blood product transfusion was strongly associated with genotype 1b. Genotype 2a was detected only among those infected by male‐to‐male sexual contact. The distribution of HCV subtypes suggests that the city plays a crucial role as a hub of HCV transmission in China. Exposure to multiple risk factors associated with HCV transmission was common among patients co‐infected with HIV and HCV. J Med. Virol. 85:1712–1723, 2013. © 2013 Wiley Periodicals, Inc.